PENGARUH PAPARAN MEDAN MAGNET ELF TERHADAP PH, MASSA JENIS, DAN KUALITAS FISIK DAGING IKAN PATIN - Firdausyiah, Wildatul; Sudarti, Sudarti; Yushardi, Yushardi (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2026)
Patin fish is one of the leading freshwater fish commodities and is highly perishable. This study aimed to examine the effect of exposure to ELF electromagnetic fields with intensities of 500 µT and 1500 µT for 120 minutes on the pH, density, and physical quality of patin fish meat. The study employed an experimental design using a RAL design. The samples consisted of 50 catfish fillets, divided into two groups: a control group without exposure and an experimental group exposed to ELF magnetic fields. Measurements of pH, density, and physical quality were taken at 0, 12, 18, and 24 hours after exposure. The analytical methods included descriptive analysis and the Shapiro-Wilk test. Additionally, the Kruskal-Wallis test and the Mann-Whitney test were performed using SPSS. The results showed that exposure to an ELF magnetic field with an intensity of 1500 µT for 120 minutes was most effective in maintaining the pH, density, and physical quality of catfish meat.